Childbirth - Jovandaric, Miljana Z.; Milenkovic, Svetlana J. (IntechOpen, 2020)
In 2015, there were about 135 million births globally. Each year, complications from pregnancy and childbirth result in about 500,000 maternal deaths, 7 million women have serious long-term problems, and 50 million women have negative health outcomes following delivery. Most of these occur in the developing world. This book discusses many aspects of childbirth and provides recommendations for improving maternal and fetal health. Chapters covers such topics as placental abruption, induced labor, low birth weight, prenatal education programs, and improving the birth space. Authors examine effects of air pollution, consanguineous marriage, and the use of traditional birth attendants on maternal morbidity and mortality.